Role of the inhibitor of serine peptidase 2 (ISP2) of Trypanosoma brucei rhodesiense in parasite virulence and modulation of the inflammatory responses of the host. - David Jessula Levy; Amy Goundry; Raquel S S Laires; Tatiana F R Costa; Carlos Mendes Novo; Dennis J Grab; Jeremy C Mottram; Ana Paula C A Lima (Public Library of Science (PLoS), 2021)
Trypanosoma brucei rhodesiense is one of the causative agents of Human African Trypanosomiasis (HAT), known as sleeping sickness. The parasite invades the central nervous system and causes severe encephalitis that is fatal if left untreated. We have previously identified ecotin-like inhibitors of serine peptidases, named ISPs, in trypanosomatid parasitic protozoa. Here, we investigated the role of ISP2 in bloodstream form T. b. rhodesiense. We generated gene-deficient mutants lacking ISP2 (Δisp2), which displayed a growth profile in vitro similar to that of wild-type (WT) parasites. C57BL/6 mice infected with Δisp2 displayed lower blood parasitemia, a delayed hind leg pathological phenotype and survived longer. The immune response was examined at two time-points that corresponded with two peaks of parasitemia. At 4 days, the spleens of Δisp2-infected mice had a greater percentage of NOS2+ myeloid cells, IFN-γ+-NK cells and increased TNF-α compared to those infected with WT and parasites re-expressing ISP2 (Δisp2:ISP2). By 13 days the increased NOS2+ population was sustained in Δisp2-infected mice, along with increased percentages of monocyte-derived dendritic cells, as well as CD19+ B lymphocytes, and CD8+ and CD4+ T lymphocytes. Taken together, these findings indicate that ISP2 contributes to T. b. rhodesiense virulence in mice and attenuates the inflammatory response during early infection.